New Species and New Records of Costa Rican Freshwater Fishes with a Tentative List of Species - Bussing, William A. (1966)
In examining the collections, I have encountered five undescribed species and 14 species that are new to the fauna of Costa Rica. Two of the aboye new records are not induded in this report for their identifications are still uncertain; however, it is time that the other species are described and reported due to the zoogeographic significance of the area and in view of recent related studies (MILLER, 17; LOFTIN, 12)